A NEW APPROACH FOR THE TSUNAMI PREDICTION USING SATELLITE ALTIMETRY: TRIALS FOR ACEH TSUNAMI EVENTS IN 2004 AND 2005 - Susumu Kanno; Yasuo Furushima; I Wayan Nuarsa; I Gede Hendrawan (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2006)
Change in the sea surface height anomaly derived from satellite altimeter was examined and applied to evaluate the possibility of tsunami prediction before the occurance. Sea surface height anomaly was composed period during earthquake and tsunami occurance. Daily variability in the sea surface height anomaly was traced about the location of hypocenter, aftershock, and the end of erthquakes from satellite altimetry. Results shows that there are the locations where the sea surface height anomaly suddenly increased or decreased before tsunami event at least. This result can be utilized and applied for the development in not only the stunami monitoting system as the disaster monitoring, but also for the effective tsunami prediction system in the near future. Keywords: tsunami, earthquake, bottom topography, sea surface height, satellite altimetry, altimeter, disaster prevention.